PENGARUH KOMPONEN PARIWISATA TERHADAP KEPUTUSAN BERKUNJUNG DI LAWANG SEWU SEMARANG - Herman Novry Kristiansen Paninggiran; Rubyah Hutomo; Heri Prabowo; Rachmaditya Perdana Kusuma Kresna (Universitas Semarang, 2020)
Lawang Sewu is a tourist attraction in Semarang City and one of the historic buildings of the Dutch Colonial Government that was originally used as the headquarters of Nederlandsch Indische Spoorweg Maatschappij commonly abbreviated as NIS or NISM, Railway Company in the Dutch East Indies. As one of the important tourism sites in Semarang City, it is important to understand what influences tourist to visit Lawang Sewu Semarang. Consequently, this research focuses on understanding the attraction, amenities and activities of Lawang Sewu that may influence a tourist decision to visit. We used a quantitative numerical data method processed by a statistical method to determine the influence of individual tourism components that influence the decision to visit Lawang Sewu. A random non-probability sampling survey was employed. Our results shows that the variable of attraction and activity have positive and significant influence to the decision of visiting Lawang Sewu Semarang while the amenities variable has no positive and significant influence on the decision of visiting Lawang Sewu.